THE USE OF AUDIOVISUAL MEDIA TO INCREASE THE STUDENTS’ VOCABULARY: A CASE OF THE TENTH GRADE STUDENTS OF SMA N 1 CEPIRING KENDAL - Rudi Hartono (ETERNAL (English Teaching Journal), 2013)
This study is concerned with teaching vocabulary by using audiovisual media. The objectives of this final project are 1) to find out the students’ vocabulary taught without using audiovisual media, 2) to find out the students’ vocabulary taught using audiovisual media, 3) to find out significance difference between the students’ vocabularywho are taught by using audiovisual media and those taught without using audiovisual media. The population of this study is the tenth grade students of SMA N 1 Cepiring Kendal. The researcher takes two classes as the subject of thisresearch. The classes are X IIS 3 and XIIS 4. They are divided into experimental group (X IIS 3) and control group (X IIS 4). The researcher uses test to get the data. The test consists of two tests, they are pre-test and post-test. From the data analysis, the researcher obtains the mean score both the experimentaland control groups. The mean score of thepre-test in the experimental group is 56.71, while the mean score of the post-test in the experimental group is 75.42. The improvement in the experimental group is 18.42. The mean score of the pre-test in the control group is 52.85, while the mean score ofthe post-test in the control group is 61.00. The improvement in the control group is 8.15.The result of t-test is 8.01, while the value of t-table is 2.00. It means that the value of t-test is higher than t-table (8.01 > 2.00). From the data above, it can be concluded that there are significant difference between the students’ who are taught by using audiovisual media and taught without using audiovisual media. The data proves that it is affective to use audiovisual mediato increase students’ vocabulary ability.